2022
DOI: 10.16899/jcm.1125489
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen in Luteal Phase Support: Effects on IVF-ICSI Antagonist Protocol Pregnancy Results

Abstract: Aim: This study aimed to investigate the effect of luteal phase support (LPS) with estradiol in addition to progesterone on pregnancy outcomes in patients who underwent ovulation induction with GnRH antagonist protocol in in vitro fertilization- intracytoplasmic sperm injection (IVF-ICSI). Materials and Methods: This retrospective study was carried out at reproductive medicine center of Necmettin Erbakan University Meram Medical Faculty. The study enrolled 128 patients undergoing ICSI on an antagonist pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Regarding ovarian stimulation outcomes, the number of embryos transferred on day five of oocyte retrieval differed significantly between the groups, with single embryo transfer in 31.1% of the progesterone-only group and 68% in the estradiol + progesterone group, while two embryos were transferred in 66.9% of the progesterone-only group and 31% in the estradiol + progesterone group. However, there was no statistically significant difference in the number of frozen embryos between the two groups, in agreement with a study conducted at 2022 [4] while in another study, (1) they found no significant difference in the number of embryo transfers between the progesterone and estrogen groups [1,4].…”
Section: Table (6)supporting
confidence: 89%
See 4 more Smart Citations
“…Regarding ovarian stimulation outcomes, the number of embryos transferred on day five of oocyte retrieval differed significantly between the groups, with single embryo transfer in 31.1% of the progesterone-only group and 68% in the estradiol + progesterone group, while two embryos were transferred in 66.9% of the progesterone-only group and 31% in the estradiol + progesterone group. However, there was no statistically significant difference in the number of frozen embryos between the two groups, in agreement with a study conducted at 2022 [4] while in another study, (1) they found no significant difference in the number of embryo transfers between the progesterone and estrogen groups [1,4].…”
Section: Table (6)supporting
confidence: 89%
“…Endometrial thickness, assessed by ultrasound examination, is commonly used as a marker of endometrial receptivity (p>0.05). However, this finding contrasts with studies conducted at 2020 and 2022 which reported a significant difference in endometrial thickness between estradiol and control groups [1,4] , differences in endometrial thickness between estradiol+progesterone and progesterone-only groups, potentially may impact pregnancy outcomes [4].…”
Section: Table (6)mentioning
confidence: 63%
See 3 more Smart Citations